Panis et circencis: o movimento tropicalista contado em programa radiofônico - Maia, Luiz Paulo (2011)
The purpose of this thesis is to show the importance of the resumption of Tropicalismo evolutionary line of Brazilian popular music. He was also one of the most important cultural movements throughout history. Using the bibliographic record deal and try to show all stages of building the movement following the trajectory of the main leaders, especially Caetano Veloso and Gilberto Gil, since they met in Salvador in the early 60s, before coming to Sao Paulo and Rio de Janeiro. Although the 1964 coup the two capitals lived an effervescent period in the cultural field, especially in film, visual arts and theater. The importance of bossa-nova, the concrete poetry of Campos brothers and Decio Pignatari and contact with avant-garde artists from other areas - especially Helio Oiticica, Glauber Rocha and José Celso Martinez ended up providing the elements of modernity in the present motion. The explosion at Festival da Record 1967, with the shock of the public and critics to see the stage with Brazilian music accompaniment of electric instruments, as well as plastic and garish clothes, totally contrary to the established order. The rant of Caetano Festival in 1968, burying a move that was not understood at the time, both the right and left. Present Tropicalismo in radio program aims to show the importance of this was the first major vehicle of mass communication and that is the least studied of all with regard to their language. Despite all the technological developments, programming on nearly all radio stations to resume the presentation of news, traffic information, weather forecast and mere turntable. From the theories of Janet el Haouli try to show the richness of the radio, today reduced the text to speech verb-oral route